Age related variation of health markers in Asian elephants - Reichert Sophie; Berger Vérane; Dos Santos Diogo João Franco; Lahdenperä Mirkka; Nyein U. Kyaw; Htut Win; Lummaa Virpi (Elsevier Inc., 2022)
Although senescence is often observed in the wild, its underlying mechanistic causes can rarely be studied alongside its consequences, because data on health, molecular and physiological measures of senescence are rare. Documenting how different age-related changes in health accelerate ageing at a mechanistic level is key if we are to better understand the ageing process. Nevertheless, very few studies, particularly on natural populations of long-lived animals, have investigated age-related variation in biological markers of health and sex differences therein. Using blood samples collected from semi-captive Asian elephants, we show that pronounced differences in haematology, blood chemistry, immune, and liver functions among age classes are also evident under natural conditions in this extremely long-lived mammal. We provide strong support that overall health declined with age, with progressive declines in immune and liver functions similarly in both males and females. These changes parallel those mainly observed to-date in humans and laboratory mammals, and suggest a certain ubiquity in the ageing patterns.